Treatment Tactics in Case of Infectious Complications in Patients with Combat Injuries of the Musculoskeletal System (according to the Clinic’s Own Experience) - Hrytsai, M.P.; Poliachenko, Yu.V.; Tsokalo, V.M.; Kolov, H.B.; Yevlantieva, T.A. (TERRA ORTHOPAEDICA, 2023)
Background. The successful treatment of combat wounds should be based on strict scientific principles, based not only on the time limits for successful wound healing, but also on the quality and scope of the measures taken, the logistics of follow-up, diagnosis and treatment, the quality of dressings and postoperative care, and a clear understanding of the treatment plan – preventive measures and sequence of evacuation of the wounded. Objective: to determine the scope and choice of optimal treatment tactics for combat injuries in patients during the war in Ukraine since 2014, who had infectious complications from the musculoskeletal system. Materials and Methods. The medical histories of patients who were treated with infectious complications at the clinic of bone-purulent surgery of the SI "Institute of Traumatology and Orthopedics of NAMS of Ukraine" from 2014 to mid2022 were analyzed. Results and Conclusions. The treatment of infectious complications of a combat injury is more intensive, protracted, and more costly in terms of resources and material. The plan covers staged treatment using various surgical procedures and techniques.